Nonaqueous electrolyte secondary battery
By using sulfonic acid compounds and silicon-containing materials in the positive electrode and negative electrode active materials of the nonaqueous electrolyte secondary battery, the problem of difficult to achieve high capacity and excellent charge and discharge cycle characteristics in the prior art is solved, and efficient battery performance is achieved.
Patent Information
- Application Number
- CN202380060077.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-26
- Filing Date
- 2023-07-28
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to achieve high capacity and excellent charge and discharge cycle characteristics simultaneously in non-aqueous electrolyte secondary batteries.
The sulfonic acid compound is attached to the surface of particles of the lithium-containing composite oxide in the positive electrode active material, and the silicon-containing material is used in the negative electrode active material, with a ratio of 3 mass% or more and a discharge capacity of 380 mAh/g or more.
The charging and discharging cycle characteristics are improved while achieving high capacity, suppressing the deterioration of the positive electrode, and ensuring that the charging and discharging capacity of the battery is specified in the negative electrode.
Smart Images

Figure CN119731823A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a nonaqueous electrolyte secondary battery. Background Art
[0002] Patent document 1 proposes that Li4Ti5O 12 An active material having a surface layer composed of a lithium sulfonate compound formed on the surface of lithium titanate particles as a main component, Patent Document 1 discloses that the use of this active material in a negative electrode active material can suppress changes in resistance of a battery before and after charge storage.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2018-6164 Summary of the invention
[0006] In non-aqueous electrolyte secondary batteries, it is an important issue to improve charge-discharge cycle characteristics while ensuring high capacity. The prior art including Patent Document 1 cannot fully address such issues, and there is still much room for improvement.
[0007] The nonaqueous electrolyte secondary battery disclosed in the present invention is a nonaqueous electrolyte secondary battery comprising a positive electrode, a negative electrode and a nonaqueous electrolyte, wherein the positive electrode comprises a lithium-containing composite oxide and a sulfonic acid compound present on the surface of particles of the composite oxide, the sulfonic acid compound being a compound represented by formula (I), and the negative electrode comprises at least a silicon-containing material as a negative electrode active material, the proportion of the silicon-containing material in the negative electrode active material is 3% by mass or more, and the discharge capacity of the negative electrode active material is 380 mAh / g or more.
[0008]
[0009] (In the formula, A is a Group 1 or Group 2 element, R is a hydrocarbon group, and n is 1 or 2.)
[0010] The nonaqueous electrolyte secondary battery disclosed herein has a high capacity and is excellent in charge and discharge cycle characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 It is a cross-sectional view of a nonaqueous electrolyte secondary battery as an example of the embodiment. DETAILED DESCRIPTION
[0012] Even if the lithium titanate described in Patent Document 1 is used for the positive electrode, the reaction potential is low and the battery capacity will decrease. The research results of the present inventors show that by making the sulfonic acid compound shown in the above formula (I) present on the particle surface of the lithium-containing composite oxide used as the positive electrode active material, a non-aqueous electrolyte secondary battery with high capacity and low resistance can be achieved. It is believed that the reason is that the reaction resistance in the positive electrode is reduced by the function of the sulfonic acid compound, and the charge and discharge depth can be deepened. However, as the charge and discharge depth deepens due to the reduction of the reaction resistance, a new problem such as a reduction in charge and discharge cycle characteristics is generated.
[0013] Therefore, the inventors of the present invention have conducted further in-depth research, using a lithium-containing composite oxide having a specific sulfonic acid compound attached to the particle surface as a positive electrode active material, and containing a silicon-containing material at a ratio of 3% by mass or more in the negative electrode active material, thereby successfully ensuring high capacity while improving the charge and discharge cycle characteristics. It is believed that according to the non-aqueous electrolyte secondary battery disclosed in the present invention, the degradation of the positive electrode is suppressed, and thus the charge and discharge cycle characteristics are improved. It is speculated that by making the negative electrode contain a silicon-containing material, the capacity of the negative electrode is increased, thereby the charge and discharge capacity of the battery is regulated in the negative electrode, and the degradation of the positive electrode is suppressed.
[0014] Hereinafter, an example of an embodiment of the non-aqueous electrolyte secondary battery disclosed in the present invention will be described in detail with reference to the accompanying drawings. It should be noted that the configuration formed by selectively combining the various constituent features of the multiple embodiments and variants described below is included in the scope of the present invention. It should be noted that in this specification, "~" refers to a range including the upper and lower limits before and after "~".
[0015] Hereinafter, as a non-aqueous electrolyte secondary battery, a cylindrical battery in which a wound electrode body 14 is housed in an outer can 16 having a bottomed cylindrical shape is exemplified, but the outer shell of the battery is not limited to a cylindrical outer can. The non-aqueous electrolyte secondary battery disclosed herein may be, for example, a square battery having a square outer can, a coin-shaped battery having a coin-shaped outer can, or a bag-shaped battery having an outer shell composed of a laminate sheet including a metal layer and a resin layer. In addition, the electrode body is not limited to a wound type, and may also be a stacked electrode body in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked with a separator.
[0016] Figure 1 FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 as an example of an embodiment. Figure 1As shown, the nonaqueous electrolyte secondary battery 10 includes a wound electrode body 14, a nonaqueous electrolyte, and an outer can 16 for storing the electrode body 14 and the nonaqueous electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 interposed therebetween. The outer can 16 is a metal container in a bottomed cylindrical shape with one end side open in the axial direction, and the opening of the outer can 16 is blocked by a sealing body 17. In the following, for convenience of description, the sealing body 17 side of the battery is set as the upper side, and the bottom side of the outer can 16 is set as the lower side.
[0017] The non-aqueous electrolyte has lithium ion conductivity and may be a liquid electrolyte (electrolyte) or a solid electrolyte.
[0018] Liquid electrolyte (electrolyte) comprises non-aqueous solvent and electrolyte salt dissolved in non-aqueous solvent. Non-aqueous solvent can use ester, ether, nitrile, amide and their mixed solvent of more than 2 kinds etc. for example. As an example of non-aqueous solvent, ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC) and their mixed solvent etc. can be listed. Non-aqueous solvent can also contain halogen substitution (for example, fluoroethylene carbonate etc.) formed by at least a part of hydrogen of these solvents being replaced by halogen atoms such as fluorine. Electrolyte salt uses lithium salt such as LiPF6 for example.
[0019] As a solid electrolyte, for example, a solid or gel-like polymer electrolyte, an inorganic solid electrolyte, etc. can be used. As an inorganic solid electrolyte, a well-known material in a fully solid lithium-ion secondary battery, etc. (for example, an oxide-based solid electrolyte, a sulfide-based solid electrolyte, a halogen-based solid electrolyte, etc.) can be used. The polymer electrolyte, for example, comprises a lithium salt and a matrix polymer, or comprises a non-aqueous solvent, a lithium salt and a matrix polymer. As a matrix polymer, for example, a polymer material that absorbs a non-aqueous solvent for gelation is used. As polymer materials, fluororesins, acrylic resins, polyether resins, etc. can be listed.
[0020] The positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode body 14 are all strip-shaped long bodies, and are alternately stacked in the radial direction of the electrode body 14 by being wound into a spiral shape. The negative electrode 12 is formed to be one circle larger than the positive electrode 11 to prevent the precipitation of lithium. That is, the negative electrode 12 is formed longer than the positive electrode 11 in the length direction and the width direction. The separator 13 is formed to be at least one circle larger than the positive electrode 11, for example, two sheets are arranged in a manner of clamping the positive electrode 11. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.
[0021] Insulating plates 18 and 19 are disposed above and below the electrode body 14, respectively. Figure 1 In the example shown, the positive electrode lead 20 extends to the sealing body 17 side through the through hole of the insulating plate 18, and the negative electrode lead 21 extends to the bottom side of the outer can 16 through the outer side of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, that is, the cover 27 electrically connected to the internal terminal plate 23 serves as the positive terminal. The negative electrode lead 21 is connected to the bottom inner surface of the outer can 16 by welding or the like, and the outer can 16 serves as the negative terminal.
[0022] A gasket 28 is provided between the outer can 16 and the sealing body 17 to ensure the airtightness inside the battery. A groove portion 22 is formed in the outer can 16, in which a part of the side portion protrudes inward and supports the sealing body 17. The groove portion 22 is preferably formed in an annular shape along the circumferential direction of the outer can 16, and the sealing body 17 is supported by its upper surface. The sealing body 17 is fixed to the upper part of the outer can 16 through the groove portion 22 and the open end of the outer can 16 fastened to the sealing body 17.
[0023] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26 and a cover 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and an insulating member 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat release, the lower valve body 24 is deformed and broken in a manner that pushes the upper valve body 26 toward the cover 27 side, thereby cutting off the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and the gas is discharged from the opening of the cover 27.
[0024] Hereinafter, the positive electrode 11 , the negative electrode 12 , and the separator 13 constituting the electrode body 14 , in particular, the positive electrode active material constituting the positive electrode 11 and the negative electrode active material constituting the negative electrode 12 will be described in detail.
[0025] [positive electrode]
[0026] The positive electrode 11, for example, has a positive electrode core 30 and a positive electrode mixture layer 31 disposed on the surface of the positive electrode core 30. The positive electrode core 30 can be made of a foil of a metal such as aluminum that is stable within the potential range of the positive electrode 11, a thin film of the metal disposed on the surface, or the like. The positive electrode mixture layer 31 contains a positive electrode active material, a conductive agent, and a binder, and is preferably disposed on both sides of the positive electrode core 30 except for a portion connected to the positive electrode lead 20. The positive electrode 11 is manufactured, for example, by applying a positive electrode mixture slurry containing a positive electrode active material, a conductive agent, and a binder to the surface of the positive electrode core 30, drying the coating, and then compressing the coating to form the positive electrode mixture layer 31 on both sides of the positive electrode core 30.
[0027] As the conductive agent contained in the positive electrode mixture layer 31, carbon black such as acetylene black and Ketjen black, graphite, carbon nanotubes (CNT), carbon nanofibers, graphene and other carbon materials can be exemplified. As the binder contained in the positive electrode mixture layer 31, fluorine-containing resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, etc. can be exemplified. In addition, these resins can also be used in combination with carboxymethyl cellulose (CMC) or its salt, polyethylene oxide, etc. The content of the conductive agent and the binder is, for example, 0.1% by mass to 5% by mass relative to the mass of the positive electrode mixture layer 31.
[0028] The positive electrode 11 includes a lithium-containing composite oxide and a sulfonic acid compound present on the surface of the composite oxide particles. The lithium-containing composite oxide with the sulfonic acid compound attached to the particle surface functions as a positive electrode active material. The sulfonic acid compound is a compound represented by formula (I).
[0029]
[0030] In the formula, A is a Group 1 or Group 2 element, R is a hydrocarbon group, and n is 1 or 2.
[0031] The sulfonic acid compound represented by formula (I) (hereinafter sometimes simply referred to as "sulfonic acid compound") reduces the reaction resistance in positive electrode 11 and improves the output characteristics of the battery. In addition, the lowering of resistance allows a longer charge and discharge depth, and thus enables a higher capacity.
[0032] From the viewpoint of increasing the capacity, the amount of the sulfonic acid compound present on the surface of the lithium-containing composite oxide is preferably 0.1% by mass or more and 1% by mass or less relative to the mass of the lithium-containing composite oxide.
[0033] The positive electrode active material mainly comprises a lithium-containing composite oxide having a sulfonic acid compound attached to the particle surface, that is, a composite particle, or may be substantially composed of only the composite particle. It should be noted that the positive electrode active material may also contain a composite oxide or other compound other than the composite particle within the scope of not impairing the purpose of the present disclosure.
[0034] The lithium-containing composite oxide preferably has a layered rock salt structure. As the layered rock salt structure of the lithium-containing composite oxide, for example, a layered rock salt structure belonging to the space group R-3m, a layered rock salt structure belonging to the space group C2 / m, etc. can be cited. Among them, from the viewpoint of high capacity and stability of the crystal structure, a layered rock salt structure belonging to the space group R-3m is preferred. The layered rock salt structure of the lithium-containing composite oxide includes a transition metal layer, a Li layer and an oxygen layer.
[0035] The lithium-containing composite oxide is a composite oxide containing metal elements such as Ni, Co, Al, and Mn in addition to Li. The metal elements constituting the lithium-containing composite oxide are, for example, Ni, Co, and M (M is at least one element selected from the group consisting of Al, Mn, Fe, Ti, Si, Nb, Mo, W, and Zn). Among them, it is preferred to contain at least one selected from Ni, Co, Al, and Mn. As an example of a suitable composite oxide, a composite oxide containing Ni, Co, and Al and a composite oxide containing Ni, Co, and Mn can be cited.
[0036] From the viewpoint of high capacity, the lithium-containing composite oxide preferably contains 80 mol% or more of Ni relative to the total molar number of metal elements other than Li. In addition, the effect of adding the sulfonic acid compound is more significant when a lithium-containing composite oxide with a high Ni content is used. The Ni content relative to the total molar number of metal elements other than Li can be 87 mol% or more, or 90 mol% or more. The upper limit of the Ni content is, for example, 95 mol%.
[0037] As described above, an example of a suitable lithium-containing composite oxide is a composite oxide containing Ni, Co and M. The content of Co is, for example, 0 mol% to 20 mol% relative to the total molar number of metal elements other than Li. The content of M is, for example, 0 mol% to 20 mol% relative to the total molar number of metal elements other than Li. Co may not be substantially added, but battery performance is improved by adding a small amount of Co. M preferably includes at least one of Mn and Al.
[0038] For example, a lithium-containing composite oxide is a general formula Li a Ni x Co y M z O 2-b (wherein, 0.95≤a≤1.2, 0.80≤x≤0.95, 0≤y≤0.20, 0≤z≤0.20, 0≤b≤0.05, x+y+z=1, and M is at least one element selected from the group consisting of Al, Mn, Fe, Ti, Si, Nb, Mo, W, and Zn.) The x in the above general formula is preferably 0.87≤x≤0.95.
[0039] The content of elements constituting the lithium-containing composite oxide can be measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES), an electron probe microanalyzer (EPMA), an energy dispersive X-ray analyzer (EDX), or the like.
[0040] The lithium-containing composite oxide is, for example, a secondary particle formed by the aggregation of multiple primary particles. The volume-based median particle size (D50) of the composite oxide is not particularly limited, and as an example, it is 3 μm to 30 μm, preferably 5 μm to 25 μm. In the case where the composite oxide is a secondary particle formed by the aggregation of primary particles, the D50 of the composite oxide refers to the D50 of the secondary particle. D50 refers to the particle size at which the cumulative frequency from the smaller particle size in the volume-based particle size distribution becomes 50%, also known as the median diameter. The particle size distribution of the composite oxide (the same is true for the negative electrode active material) is measured using a laser diffraction particle size distribution measuring device (for example, Microtrac Bell Inc., MT3000II) and water as the dispersion medium.
[0041] The average particle size of primary particles constituting the lithium-containing composite oxide is, for example, 0.05 μm to 1 μm. The average particle size of the primary particles is calculated by averaging the diameters of circumscribed circles of the primary particles obtained by analyzing a scanning electron microscope (SEM) image of a cross section of secondary particles.
[0042] As described above, the sulfonic acid compound present on the surface of the particles of the lithium-containing composite oxide is a compound represented by formula (I).
[0043]
[0044] In the formula, A is an element of Group 1 or Group 2, R is a hydrocarbon group, and n is 1 or 2. A is preferably an element of Group 1. Among them, Li or Na is more preferred, and Li is particularly preferred.
[0045] In formula (I), R is preferably an alkyl group. The carbon number of the alkyl group is preferably 5 or less, more preferably 3 or less. From the viewpoint of reducing the reaction resistance, an example of a suitable R is an alkyl group having a carbon number of 3 or less, wherein a methyl group is preferred. It should be noted that, in R, a portion of the hydrogen bonded to the carbon may also be substituted by fluorine. In addition, n in formula (I) is preferably 1.
[0046] Specific examples of the sulfonic acid compound include lithium methanesulfonate, lithium ethanesulfonate, lithium propanesulfonate, sodium methanesulfonate, sodium ethanesulfonate, magnesium methanesulfonate, lithium fluoromethanesulfonate, etc. Among them, at least one selected from the group consisting of lithium methanesulfonate, lithium ethanesulfonate and sodium methanesulfonate is preferred, and lithium methanesulfonate is particularly preferred.
[0047] The sulfonic acid compound is present, for example, homogeneously on the entire surface of the particles of the lithium-containing composite oxide. The presence of the sulfonic acid compound on the surface of the particles of the lithium-containing composite oxide can be confirmed by Fourier transform infrared spectroscopy (FT-IR). In the infrared absorption spectrum obtained by FT-IR, the positive electrode active material containing lithium methanesulfonate, for example, has a peak at 1238 cm -1 、1175cm -1、1065cm -1 、785cm -1 There is an absorption peak near
[0048] 1238cm -1 、1175cm -1 、1065cm -1 The peaks near 785cm are caused by the SO stretching vibration of lithium methanesulfonate. -1 The nearby peaks are peaks derived from CS stretching vibration of lithium methanesulfonate.
[0049] For positive electrode active materials containing sulfonic acid compounds other than lithium methanesulfonate, the presence can also be confirmed by the absorption peak derived from the sulfonic acid compound in the infrared absorption spectrum. It should be noted that the presence of the sulfonic acid compound on the surface of the particles of the lithium-containing composite oxide can also be confirmed by ICP, atomic absorption spectroscopy, X-ray photoelectron spectroscopy (XPS), radioactive light XRD measurement, TOF-SIMS, etc.
[0050] The positive electrode active material as an example of the embodiment can be produced by the following method. It should be noted that the production method described here is an example, and the production method of the positive electrode active material is not limited to this method.
[0051] First, a metal oxide containing metal elements such as Ni, Co, Al, and Mn is synthesized. Then, the metal oxide and a lithium compound are mixed and calcined to obtain a lithium-containing composite oxide. The metal oxide is synthesized, for example, by stirring a solution of a metal salt containing Ni, Co, Al, Mn, etc. while dropping an alkaline solution such as sodium hydroxide, adjusting the pH to the alkaline side (for example, 8.5 to 12.5), thereby precipitating a composite hydroxide containing metal elements such as Ni, Co, Al, and Mn (coprecipitation), and heat-treating the composite hydroxide to synthesize the metal oxide. The heat treatment temperature is not particularly limited, and as an example, it is 300°C to 600°C.
[0052] Examples of lithium compounds include Li2CO3, LiOH, Li2O2, Li2O, LiNO3, LiNO2, Li2SO4, LiOH·H2O, LiH, and LiF. The metal oxide and the lithium compound are mixed, for example, in a molar ratio of the metal element in the metal oxide to Li in the lithium compound of 1:0.98 to 1:1.1. It should be noted that when mixing the metal oxide and the lithium compound, other metal raw materials may be added as needed.
[0053] The mixture of the metal oxide and the lithium compound is calcined, for example, in an oxygen atmosphere. The mixture may also be calcined through multiple temperature rising processes. The calcining process includes: a first temperature rising process of heating to 450°C to 680°C at a temperature rising rate of, for example, 1.0°C / min to 5.5°C / min, and a second temperature rising process of heating to a temperature exceeding 680°C at a temperature rising rate of 0.1°C / min to 3.5°C / min. The maximum reaching temperature of the calcining process may be set to 700°C to 850°C, and may be maintained at this temperature for 1 hour to 10 hours.
[0054] Next, the calcined product (containing lithium composite oxide) is washed with water and dehydrated to obtain a cake-like composition. The residual alkali component is removed by this washing process. The washing and dehydration can be carried out by existing known methods. Next, the cake-like composition is dried to obtain a powdery composition. The drying process can also be carried out under a vacuum atmosphere. An example of drying conditions is 0.5 hours to 15 hours at a temperature of 150°C to 400°C.
[0055] The sulfonic acid compound is added to the cake-like composition obtained in the washing step, for example, or to the powder-like composition obtained in the drying step. At this time, a sulfonic acid solution may be added instead of the sulfonic acid compound or together with the sulfonic acid compound. Thus, a positive electrode active material having a sulfonic acid compound attached to the surface of particles of the lithium-containing composite oxide can be obtained. The sulfonic acid compound may be added as an aqueous dispersion. In addition, the sulfonic acid solution is preferably an aqueous solution of sulfonic acid. The concentration of sulfonic acid in the sulfonic acid solution is, for example, 0.5% by mass to 40% by mass.
[0056] Note that, since a certain amount of lithium compound remains in the cake-like composition, by adding the sulfonic acid solution to the cake-like composition, Li dissolved in water in the cake reacts with the sulfonic acid to obtain lithium sulfonate.
[0057] [negative electrode]
[0058] The negative electrode 12, for example, has a negative electrode core 40 and a negative electrode mixture layer 41 disposed on the surface of the negative electrode core 40. The negative electrode core 40 can be made of a foil of a metal such as copper that is stable within the potential range of the negative electrode 12, a thin film of the metal disposed on the surface, or the like. The negative electrode mixture layer 41 contains a negative electrode active material and a binder, and is preferably disposed on both sides of the negative electrode core 40 except for the portion connected to the negative electrode lead 21. The negative electrode 12 is manufactured, for example, by applying a negative electrode mixture slurry containing a negative electrode active material and a binder to the surface of the negative electrode core 40, drying the coating, and then compressing the coating to form the negative electrode mixture layer 41 on both sides of the negative electrode core 40. It should be noted that the negative electrode mixture layer 41 may further contain a conductive agent such as CNT.
[0059] Examples of the binder included in the negative electrode mixture layer 41 include styrene butadiene rubber (SBR), nitrile rubber (NBR), carboxymethyl cellulose (CMC) or its salt, polyacrylic acid (PAA) or its salt (PAA-Na, PAA-K, etc., or partially neutralized salt), polyvinyl alcohol (PVA), etc. These may be used alone or in combination of two or more.
[0060] The negative electrode 12 contains at least a silicon-containing material as a negative electrode active material, and the proportion of the silicon-containing material in the negative electrode active material is 3% by mass or more. As a result, the degradation of the positive electrode is suppressed, so it is considered that the charge-discharge cycle characteristics are improved. The proportion of the silicon-containing material in the negative electrode active material is, for example, 3% by mass or more and 20% by mass or less.
[0061] The silicon-containing material is a material containing Si, and as an example, silicon alloys, silicon compounds, and composite materials containing Si can be cited. Among them, composite materials containing Si are preferred. The D50 of the composite material is usually smaller than the D50 of graphite. The volume-based D50 of the composite material is, for example, 1 μm to 15 μm. It should be noted that the silicon-containing material can be used alone or in combination of two or more.
[0062] Suitable silicon-containing materials (the above-mentioned composite materials) are composite particles containing an ion-conducting phase and a Si phase dispersed in the ion-conducting phase. The ion-conducting phase is, for example, at least one selected from the group consisting of a silicate phase, a carbon phase, a silicide phase, and a silicon oxide phase. The silicide phase is a phase of a compound composed of Si and an element that is more electrically positive than Si, and as an example, NiSi, Mg2Si, TiSi2, etc. can be cited. The Si phase is formed by dispersing Si into fine particles. The ion-conducting phase is a continuous phase composed of a collection of particles that are finer than the Si phase.
[0063] The average size of the Si phase is preferably 1 nm to 200 nm, more preferably 1 nm to 100 nm. The average size of the Si phase is calculated by taking an SEM image of a cross section of a particle of a silicon-containing material and averaging the diameter of the circumscribed circle of the Si phase extracted by image analysis. The average size of the Si phase may also be, for example, 1 nm to 10 nm. By reducing the size of the Si phase, it is possible to maintain a high capacity and suppress the particle expansion rate associated with charge and discharge.
[0064] The above composite material may also have a conductive layer covering the surface of the ion-conducting phase. The conductive layer is made of a material having a higher conductivity than the ion conductor, and forms a good conductive path in the negative electrode mixture layer 41. The conductive layer is, for example, a carbon coating made of a conductive carbon material. As the conductive carbon material, carbon black such as acetylene black and Ketjen black, graphite, or amorphous carbon with low crystallinity (non-crystalline carbon) can be used. Considering ensuring conductivity and the diffusibility of Li ions into the particles, the thickness of the conductive layer is preferably 1 nm to 200 nm or 5 nm to 100 nm. The thickness of the conductive layer can be measured by observing the cross-section of the composite material using SEM or a transmission electron microscope (TEM).
[0065] An example of a suitable composite material containing Si is a composite particle having an island structure in which fine Si is substantially uniformly dispersed in an amorphous silica phase and having a general formula SiO x (0 < x ≤ 2). The main component of the silica may also be silicon dioxide. In addition, Li may be doped in the silica phase. The content ratio (x) of oxygen to Si is, for example, 0.5 ≤ x < 2.0, and preferably 0.8 ≤ x ≤ 1.5.
[0066] Another example of a suitable composite material containing Si is a composite particle having an island structure in which fine Si is substantially uniformly dispersed in an amorphous silicate phase. The silicate phase contains, for example, at least one element selected from the group consisting of elements of Groups 1 and 2 of the periodic table. In addition, the silicate phase may further contain at least one element selected from the group consisting of B, Al, Zr, Nb, Ta, V, La, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F, and W.
[0067] A suitable silicate phase is a lithium silicate phase containing Li. The lithium silicate phase is, for example, a phase of a composite oxide represented by the general formula Li 2z SiO (2+z) (0 < z < 2). It is preferable that the lithium silicate phase does not contain Li4SiO4 (z = 2). Li4SiO4 is an unstable compound and reacts with water to show alkalinity, and thus sometimes deteriorates Si, resulting in a decrease in the charge-discharge capacity. From the viewpoints of stability, productivity, Li ion conductivity, etc., the lithium silicate phase preferably has Li2SiO3 (z = 1) or Li2Si2O5 (z = 1 / 2) as the main component.
[0068] Another example of a suitable composite material containing Si is a composite particle having a sea-island structure in which fine Si is roughly uniformly dispersed in a carbon phase. In at least a portion of the silicon-containing material, the ion-conducting phase is preferably a carbon phase. The carbon phase is preferably an amorphous carbon phase. The carbon phase may also contain a crystalline phase component, but preferably has more amorphous phase components. The amorphous carbon phase is composed of a carbon material whose average interplanar spacing of the (002) plane measured by X-ray diffraction exceeds 0.34 nm. It should be noted that the composite material containing the carbon phase may have a conductive layer different from the carbon phase, or may not have the conductive layer.
[0069] The discharge capacity of the negative electrode active material is preferably 380 mAh / g or more. This allows the charge and discharge capacity of the battery to be regulated in the negative electrode, and more significantly suppresses deterioration of the positive electrode.
[0070] The negative electrode 12 may further contain a carbon material as a negative electrode active material. The negative electrode 12 may also substantially contain only a carbon material and a silicon-containing material as negative electrode active materials. It should be noted that the non-aqueous electrolyte secondary battery using the positive electrode 11 using a sulfonic acid compound and the negative electrode 12 not containing a silicon-containing material may sometimes have reduced charge and discharge cycle characteristics.
[0071] The carbon material contained in the negative electrode mixture layer 41 is, for example, at least one selected from the group consisting of natural graphite, artificial graphite, soft carbon and hard carbon. Among them, it is preferred to use artificial graphite such as blocky artificial graphite (MAG), graphitized mesophase carbon microbeads (MCMB), natural graphite such as flaky graphite, blocky graphite, and earthy graphite, or a mixture thereof. The volume-based D50 of the carbon material is, for example, 1 μm to 30 μm, preferably 5 μm to 25 μm.
[0072] Soft carbon and hard carbon are classified as amorphous carbon with an underdeveloped graphite crystal structure. More specifically, it refers to a carbon component with a d(002) interplanar spacing of 0.342 nm or more based on X-ray diffraction. Soft carbon is also called graphitizable carbon, which is carbon that is easily graphitized by high temperature treatment compared to hard carbon. Hard carbon is also called difficult to graphitize carbon. It should be noted that there is no need to clearly distinguish between soft carbon and hard carbon in the composition of the present invention. As a negative electrode active material, graphite and at least one amorphous carbon of soft carbon and hard carbon can also be used in combination.
[0073] [Separator]
[0074] The separator 13 uses a porous sheet with ion permeability and insulation. As specific examples of the porous sheet, microporous films, woven fabrics, nonwoven fabrics, etc. can be listed. As the material of the separator 13, polyolefins such as polyethylene and polypropylene, cellulose, etc. are suitable. The separator 13 can be a single-layer structure or a multi-layer structure. In addition, a resin layer with high heat resistance such as aramid resin can be formed on the surface of the separator 13.
[0075] A filler layer containing an inorganic filler may also be formed at the interface between the separator 13 and at least one of the positive electrode 11 and the negative electrode 12. Examples of the inorganic filler include oxides containing metal elements such as Ti, Al, Si, and Mg, and phosphate compounds. The filler layer may be formed by applying a slurry containing the filler to the surface of the positive electrode 11, the negative electrode 12, or the separator 13.
[0076] Example
[0077] Hereinafter, the present disclosure will be further described based on examples, but the present disclosure is not limited to these examples.
[0078] <Example 1>
[0079] [Preparation of positive electrode active material]
[0080] The [Ni 0.90 Al 0.05 Mn 0.05 The composite hydroxide represented by ](OH)2 was calcined at 500°C for 8 hours to obtain an oxide (Ni 0.90 Al 0.05 Mn 0.05 Next, LiOH and the composite oxide were mixed so that the molar ratio of Li to the total amount of Ni, Al and Mn was 1.03:1 to obtain a mixture. The mixture was placed under an oxygen gas flow with an oxygen concentration of 95% (per 10 cm 3 The mixture was calcined at a rate of 2 mL / min and a flow rate of 5 L / min per kg of the mixture) from room temperature to 650°C at a heating rate of 2.0°C / min, and then calcined from 650°C to 780°C at a heating rate of 0.5°C / min to obtain a lithium-containing composite oxide.
[0081] Water is added to the obtained lithium-containing composite oxide to make the slurry concentration become 1500g / L, stirred for 15 minutes, and filtered to obtain a cake-like composition. Powdered lithium methanesulfonate is added to the cake-like composition. The amount of lithium methanesulfonate added is 0.5% by mass relative to the total mass of the lithium-containing composite oxide. After adding lithium methanesulfonate, it is dried under a vacuum atmosphere at 180°C for 2 hours to obtain a positive electrode active material. It should be noted that the presence of lithium methanesulfonate on the particle surface of the composite oxide was confirmed by Fourier transform infrared spectroscopy (FT-IR).
[0082] [Production of positive electrode]
[0083] The positive electrode active material, acetylene black and polyvinylidene fluoride are mixed in a mass ratio of 98:1:1, and N-methyl-2-pyrrolidone (NMP) is used as a dispersion medium to prepare a positive electrode mixture slurry. Next, the positive electrode mixture slurry is applied to the positive electrode core formed by aluminum foil, and after the coating is dried and compressed, the positive electrode core is cut into a specified electrode size to obtain a positive electrode having a positive electrode mixture layer formed on both sides of the positive electrode core. It should be noted that an exposed portion exposed on the surface of the positive electrode core is provided on a part of the positive electrode.
[0084] [Production of negative electrode]
[0085] Artificial graphite and SiO are mixed in a mass ratio of 97:3 and used as a negative electrode active material. 100 parts by mass of the negative electrode active material, 1 part by mass of carboxymethyl cellulose (CMC) and 1 part by mass of styrene butadiene rubber (SBR) are mixed, and an appropriate amount of water is added to prepare a negative electrode mixture slurry. Next, the negative electrode mixture slurry is applied on a negative electrode core formed of copper foil, the coating is dried, and after compression, the negative electrode core is cut into a specified electrode size, and a negative electrode having a negative electrode mixture layer formed on both sides of the negative electrode core is produced. It should be noted that an exposed portion where the surface of the negative electrode core is exposed is provided on a part of the negative electrode.
[0086] [Preparation of non-aqueous electrolyte]
[0087] LiPF6 was dissolved at a concentration of 1.2 mol / L in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of 3:3:4 (25°C) to prepare a non-aqueous electrolyte.
[0088] [Production of test battery cell (secondary battery)]
[0089] Separately, an aluminum lead is installed on the exposed portion of the positive electrode, and a nickel lead is installed on the exposed portion of the negative electrode, and the positive electrode and the negative electrode are wound into a spiral shape through a polyolefin separator, thereby making a wound electrode body. Insulating plates are respectively arranged above and below the electrode body, and the electrode body is stored in an outer can. The negative electrode lead is welded to the bottom of the outer can with a bottomed cylindrical shape, and the positive electrode lead is welded to the sealing body. The electrolyte is injected into the outer can, and the opening of the outer can is sealed through the sealing body through the gasket to make a secondary battery as a test battery unit.
[0090] [Evaluation of charge-discharge cycle characteristics (capacity retention rate after cycle test)]
[0091] The test battery cell was charged at a constant current of 0.2C until the battery voltage reached 4.2V under a temperature environment of 25°C, and then charged at a constant voltage of 4.2V until the current value reached 0.02C. Then, the battery was discharged at a constant current of 0.2C until the battery voltage reached 2.5V. This charge and discharge was regarded as one cycle, and 200 cycles were performed. The discharge capacity of the first cycle and the discharge capacity of the 200th cycle were obtained, and the capacity retention rate was calculated according to the following formula.
[0092] Capacity retention rate (%) = 200th cycle discharge capacity / 1st cycle discharge capacity × 100
[0093] <Comparative Example 1>
[0094] A test cell was produced and evaluated in the same manner as in Example 1 except that lithium methanesulfonate was not added in the production of the positive electrode active material.
[0095] <Example 2-1>
[0096] A test battery cell was prepared and evaluated in the same manner as in Example 1, except that the amount of lithium methanesulfonate added relative to the total mass of the lithium-containing composite oxide was set to 0.1 mass % in the preparation of the positive electrode active material and the mixing ratio of artificial graphite to SiO was set to 94:6 in the preparation of the negative electrode.
[0097] <Example 2-2>
[0098] In the preparation of the positive electrode active material, a test cell was prepared and evaluated in the same manner as in Example 2-1 except that the amount of lithium methanesulfonate added was 0.3 mass % based on the total mass of the lithium-containing composite oxide.
[0099] <Example 2-3>
[0100] In the preparation of the positive electrode active material, a test cell was prepared and evaluated in the same manner as in Example 2-1 except that the amount of lithium methanesulfonate added was 0.5 mass % based on the total mass of the lithium-containing composite oxide.
[0101] <Example 2-4>
[0102] In the preparation of the positive electrode active material, a test cell was prepared and evaluated in the same manner as in Example 2-1 except that the amount of lithium methanesulfonate added was 1 mass % relative to the total mass of the lithium-containing composite oxide.
[0103] <Example 2-5>
[0104] In the preparation of the positive electrode active material, sodium methanesulfonate was used instead of lithium methanesulfonate, and the addition amount of sodium methanesulfonate was set to 0.5 mass % based on the total mass of the lithium-containing composite oxide. A test cell was prepared and evaluated in the same manner as in Example 2-1.
[0105] <Example 2-6>
[0106] In the preparation of the positive electrode active material, a test cell was prepared and evaluated in the same manner as in Example 2-1 except that lithium ethanesulfonate was used instead of lithium methanesulfonate and the amount of lithium ethanesulfonate added was 0.5 mass % relative to the total mass of the lithium-containing composite oxide.
[0107] <Comparative Example 2-1>
[0108] A test cell was produced and evaluated in the same manner as in Example 2-1 except that lithium methanesulfonate was not added in the production of the positive electrode active material.
[0109] <Comparative Example 2-2>
[0110] In the preparation of the positive electrode active material, a test cell was prepared and evaluated in the same manner as in Example 2-1 except that lithium succinate was added instead of methanesulfonic acid and the amount of lithium succinate added was 0.5 mass % relative to the total mass of the lithium-containing composite oxide.
[0111] <Comparative Example 2-3>
[0112] In the preparation of the positive electrode active material, a test cell was prepared and evaluated in the same manner as in Example 2-1 except that lithium oxalate was added instead of methanesulfonic acid and the amount of lithium oxalate added was 0.5 mass % relative to the total mass of the lithium-containing composite oxide.
[0113] <Example 3>
[0114] In the preparation of the positive electrode active material and in the preparation of the negative electrode, a test cell was prepared in the same manner as in Example 1 except that the mixing ratio of artificial graphite to SiO was 85:15. Evaluation was performed.
[0115] <Comparative Example 3>
[0116] A test cell was produced and evaluated in the same manner as in Example 3 except that lithium methanesulfonate was not added in the production of the positive electrode active material.
[0117] <Example 4>
[0118] A test cell was produced and evaluated in the same manner as in Example 1 except that the mixing ratio of artificial graphite to SiO was 80:20 in the production of the positive electrode active material and in the production of the negative electrode.
[0119] <Comparative Example 4>
[0120] A test cell was produced and evaluated in the same manner as in Example 4 except that lithium methanesulfonate was not added in the production of the positive electrode active material.
[0121] <Example 5>
[0122] A test cell was produced and evaluated in the same manner as in Example 1 except that SiO was used as the negative electrode active material in the production of the positive electrode active material and in the production of the negative electrode.
[0123] <Comparative Example 5>
[0124] A test cell was produced and evaluated in the same manner as in Example 5 except that lithium methanesulfonate was not added in the production of the positive electrode active material.
[0125] <Comparative Example 6-1>
[0126] A test cell was produced and evaluated in the same manner as in Example 1 except that artificial graphite was used as the negative electrode active material in the production of the positive electrode active material and in the production of the negative electrode.
[0127] <Comparative Example 6-2>
[0128] A test cell was produced and evaluated in the same manner as in Comparative Example 6-1 except that lithium methanesulfonate was not added in the production of the positive electrode active material.
[0129] The evaluation results of the test battery cells of the embodiments and comparative examples are shown in Tables 1 to 3. In Table 1, the capacity maintenance rate of the test battery cell of Embodiment 1 is a relative value when the capacity maintenance rate of the test battery cell of Comparative Example 1 is set to 100. In Table 2, the capacity maintenance rates of the test battery cells of Embodiments 2-1 to 2-6 and Comparative Examples 2-2 and 2-3 are relative values when the capacity maintenance rate of the test battery cell of Comparative Example 2-1 is set to 100. In Table 3, the capacity maintenance rates of the test battery cells of Embodiments 3, 4, 5 and Comparative Example 6-1 are relative values when the capacity maintenance rates of the test battery cells of Comparative Examples 3, 4, 5 and Comparative Example 6-2 are set to 100, respectively. A larger capacity maintenance rate indicates better charge and discharge cycle characteristics.
[0130] [Table 1]
[0131]
[0132] [Table 2]
[0133]
[0134] [Table 3]
[0135]
[0136] In Tables 1 to 3, the test cells of the embodiments have improved capacity retention rates compared to the test cells of the comparative examples. From the results of the test cells of Examples 2-1 to 2-4 in Table 2, it can be seen that the addition amount of the methanesulfonic acid compound is about 0.5 mass %, and the improvement in the charge and discharge cycle characteristics is the greatest. In addition, from the results of the test cells of Examples 2-3, 2-5, and 2-6, it can be seen that lithium methanesulfonate is preferred as the sulfonic acid compound. On the other hand, the test cells of Comparative Examples 2-2 and 2-3, which use lithium succinate or lithium oxalate instead of the sulfonic acid compound, have charge and discharge cycle characteristics equivalent to those of the test cell of Comparative Example 2-1, in which no acid salt is added to the positive electrode. In addition, from the results of the test cells of Comparative Examples 6-1 and 6-2, it can be seen that the charge and discharge cycle characteristics of the non-aqueous electrolyte secondary battery using a negative electrode that does not contain a silicon-containing material are sometimes reduced even when a sulfonic acid compound is used in the positive electrode.
[0137] The present disclosure is further described through the following embodiments.
[0138] Composition 1:
[0139] A non-aqueous electrolyte secondary battery comprises a positive electrode, a negative electrode and a non-aqueous electrolyte.
[0140] The positive electrode comprises a lithium-containing composite oxide and a sulfonic acid compound present on the surface of particles of the lithium-containing composite oxide.
[0141] The aforementioned sulfonic acid compound is a compound represented by formula (I),
[0142] The negative electrode contains at least a silicon-containing material as a negative electrode active material, and the proportion of the silicon-containing material in the negative electrode active material is 3% by mass or more.
[0143] The negative electrode active material has a discharge capacity of 380 mAh / g or more.
[0144]
[0145] (In the formula, A is a Group 1 or Group 2 element, R is a hydrocarbon group, and n is 1 or 2.)
[0146] Composition 2:
[0147] The nonaqueous electrolyte secondary battery according to Configuration 1, wherein A is a Group 1 element.
[0148] Composition 3:
[0149] The nonaqueous electrolyte secondary battery according to Configuration 1, wherein A is Li.
[0150] Composition 4:
[0151] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 3, wherein R is an alkyl group.
[0152] Composition 5:
[0153] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 3, wherein R is a methyl group.
[0154] Composition 6:
[0155] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 5, wherein the amount of the sulfonic acid compound present on the surface of the lithium-containing composite oxide is 0.1 mass % or more and 1 mass % or less relative to the mass of the lithium-containing composite oxide.
[0156] Composition 7:
[0157] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 6, wherein the lithium-containing composite oxide has a layered rock salt structure.
[0158] Composition 8:
[0159] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 7, wherein the negative electrode further includes a carbon material as the negative electrode active material.
[0160] The carbon material is at least one selected from the group consisting of natural graphite, artificial graphite, soft carbon and hard carbon.
[0161] Composition 9:
[0162] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 8, wherein the silicon-containing material includes an ion conductive phase and a Si phase dispersed in the ion conductive phase.
[0163] Composition 10:
[0164] The nonaqueous electrolyte secondary battery according to Configuration 9, wherein the ion conductive phase is at least one selected from the group consisting of a silicate phase, a carbon phase, a silicide phase, and a silicon oxide phase.
[0165] Composition 11:
[0166] The nonaqueous electrolyte secondary battery according to configuration 9 or 10, wherein the ion conductive phase contains at least one element selected from the group consisting of Group 1 and Group 2 elements.
[0167] Composition 12:
[0168] According to the non-aqueous electrolyte secondary battery described in configuration 11, the aforementioned ion conductive phase also contains at least one element selected from the group consisting of B, Al, Zr, Nb, Ta, V, La, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F and W.
[0169] Composition 13:
[0170] The nonaqueous electrolyte secondary battery according to any one of Configurations 9 to 12, wherein in at least a portion of the silicon-containing material, the ion-conductive phase is a carbon phase.
[0171] Composition 14:
[0172] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 13, wherein a ratio of the silicon-containing material in the negative electrode active material is 3 mass % or more and 20 mass % or less.
[0173] Description of Reference Numerals
[0174] 10 non-aqueous electrolyte secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 16 outer can, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 groove portion, 23 internal terminal plate, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cover, 28 gasket, 30 positive electrode core body, 31 positive electrode mixture layer, 40 negative electrode core body, 41 negative electrode mixture layer.
Claims
1. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, The positive electrode comprises a lithium-containing composite oxide and a sulfonic acid compound present on the surface of particles of the lithium-containing composite oxide. The sulfonic acid compound is a compound represented by formula (I), The negative electrode contains at least a silicon-containing material as a negative electrode active material, and the proportion of the silicon-containing material in the negative electrode active material is 3% by mass or more. The discharge capacity of the negative electrode active material is 380 mAh / g or more, In the formula, A is a Group 1 or Group 2 element, R is a hydrocarbon group, and n is 1 or 2.
2. The nonaqueous electrolyte secondary battery according to claim 1, wherein The A is a Group 1 element.
3. The nonaqueous electrolyte secondary battery according to claim 1, wherein The A is Li.
4. The nonaqueous electrolyte secondary battery according to claim 1, wherein The R is an alkyl group.
5. The nonaqueous electrolyte secondary battery according to claim 1, wherein The R is a methyl group.
6. The nonaqueous electrolyte secondary battery according to claim 1, wherein An amount of the sulfonic acid compound present on the surface of the lithium-containing composite oxide is 0.1 mass % or more and 1 mass % or less relative to the mass of the lithium-containing composite oxide.
7. The nonaqueous electrolyte secondary battery according to claim 1, wherein The lithium-containing composite oxide has a layered rock salt structure.
8. The nonaqueous electrolyte secondary battery according to claim 1, wherein The negative electrode further comprises a carbon material as the negative electrode active material, The carbon material is at least one selected from the group consisting of natural graphite, artificial graphite, soft carbon, and hard carbon.
9. The nonaqueous electrolyte secondary battery according to claim 1, wherein The silicon-containing material includes an ion-conducting phase and a Si phase dispersed in the ion-conducting phase.
10. The nonaqueous electrolyte secondary battery according to claim 9, wherein The ion-conducting phase is at least one selected from the group consisting of a silicate phase, a carbon phase, a silicide phase, and a silicon oxide phase.
11. The nonaqueous electrolyte secondary battery according to claim 9, wherein The ion conductive phase includes at least one element selected from the group consisting of Group 1 and Group 2 elements.
12. The nonaqueous electrolyte secondary battery according to claim 11, wherein The ion conductive phase further contains at least one element selected from the group consisting of B, Al, Zr, Nb, Ta, V, La, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F and W.
13. The nonaqueous electrolyte secondary battery according to claim 9, wherein In at least a portion of the silicon-containing material, the ion-conducting phase is a carbon phase.
14. The nonaqueous electrolyte secondary battery according to claim 1, wherein The ratio of the silicon-containing material in the negative electrode active material is 3 mass % or more and 20 mass % or less.
Citation Information
Patent Citations
Lithium titanate powder for power storage device electrode, active substance material, and power storage device using the active substance material
JP2018006164A